2017
DOI: 10.1371/journal.pone.0176546
|View full text |Cite
|
Sign up to set email alerts
|

Does competition improve financial stability of the banking sector in ASEAN countries? An empirical analysis

Abstract: This study examines the influence of competition on the financial stability of the commercial banks of Association of Southeast Asian Nation (ASEAN) over the 1990 to 2014 period. Panzar-Rosse H-statistic, Lerner index and Herfindahl-Hirschman Index (HHI) are used as measures of competition, while Z-score, non-performing loan (NPL) ratio and equity ratio are used as measures of financial stability. Two-step system Generalized Method of Moments (GMM) estimates demonstrate that competition measured by H-statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
86
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(100 citation statements)
references
References 69 publications
11
86
1
2
Order By: Relevance
“…Consistent to the findings of Sango and Moussa (2017) we found positive impact of interest rate on the financial stability. Likewise Noman et al (2017) we found negative impacts of global financial crisis on financial stability.…”
Section: Estimated Results With the Baseline Modelmentioning
confidence: 53%
“…Consistent to the findings of Sango and Moussa (2017) we found positive impact of interest rate on the financial stability. Likewise Noman et al (2017) we found negative impacts of global financial crisis on financial stability.…”
Section: Estimated Results With the Baseline Modelmentioning
confidence: 53%
“…Compared with that of the semi-parametric model without intervention quality, this result is in line with the high reduction of the F statistic of this model. Therefore, if intervention quality is allowed for in a non-linear nonparametric way, the effect of competition on stability becomes neutral (Martinez-Miera & Repullo, 2010;Noman et al, 2017). This result is interpreted as evidence that the intervention quality helps "hedge" the effects of competition on stability.…”
Section: Resultsmentioning
confidence: 96%
“…The impact of competition on stability is controversial. On the other hand, because competition pulls interest rates down, deterring moral hazard and adverse selection behaviour among borrowers, and decreasing loans, it may lead to greater stability (Fu, Lin, & Molyneux, 2014;Noman, Gee, & Isa, 2017). This makes banks less able to endure demand or supply shocks and encourage undue risk-taking (Kabir & Worthington, 2017;Leroy & Lucotte, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stricter business competition has led to greater number of transactions. Both smooth financial flow and economic growth would increase the pace of business competition (Noman, Gee, & Isa, 2017)). As a result, the number of employees is increasing, and the production issues are becoming significant.…”
Section: Introductionmentioning
confidence: 99%